Determinants of aortic growth rate in patients with bicuspid aortic valve by cardiovascular magnetic resonance. Issue 2 (2nd November 2019) - Sophocleous, Froso; Berlot, Bostjan; Ordonez, Maria Victoria; Baquedano, Mai; Milano, Elena Giulia; De Francesco, Viola; Stuart, Graham; Caputo, Massimo; Bucciarelli-Ducci, Chiara; Biglino, Giovanni
Abstract : Objectives: This study aimed to identify determinants of aortic growth rate in bicuspid aortic valve (BAV) patients. We hypothesised that (1) BAV patients with repaired coarctation (CoA) exhibit decreased aortic growth rate, (2) moderate/severe re-coarctation (reCoA) results in increased growth rate, (3) patients with right non-coronary (RN) valve cusps fusion pattern exhibit increased aortic growth rate compared with right-left cusps fusion and type 0 valves. Methods: Starting from n=521 BAV patients with cardiovascular magnetic resonance data, we identified n=145 patients with at least two scans for aortic growth analysis. Indexed areas of the sinuses of Valsalva and ascending aorta (AAo) were calculated from cine images in end-systole and end-diastole. Patients were classified based on dilation phenotype, presence of CoA, aortic valve function and BAV morphotype. Comparisons between groups were performed. Linear regression was carried out to identify associations between risk factors and aortic growth rate. Results: Patients (39±16 years of age, 68% male) had scans 3.7±1.8 years apart; 32 presented with AAo dilation, 18 with aortic root dilation and 32 were overall dilated. Patients with repaired CoA (n=61) showed decreased aortic root growth rate compared with patients without CoA (p≤0.03) regardless of sex or age. ReCoA, aortic stenosis, regurgitation and history of hypertension were not associated with growth rate. RN fusion pattern showed the highest aortic root growth rate and type 0 the smallest (0.30 vs 0.08 cm 2 /m*year, end-systole, p=0.03). Conclusions: Presence of CoA and cusp fusion morphotype were associated with changes in rate of root dilation in our BAV population.